Performance, carcass and meat quality of Angus-Nellore heifers finished in integrated livestock forest systems - Oliveira Neves, F. de [UNESP]; Andrighetto, C. [UNESP]; Aparecida da Luz, P. [UNESP]; Pavan Mateus, G.; Freitas Santos, J. Mara de [UNESP]; Pereira de Lima, L. [UNESP]; Souza Sekiya, B. Midori [UNESP]; Zanetti, L. H. [UNESP]; Lupatini, G. C. [UNESP]; Vieira, N. C. [UNESP] (Kielanowski Inst Animal Physiology Nutrition, 2021)
The objective of this research was to evaluate the impact of the different shading densities on performance, carcass and meat quality of Angus-Nellore heifers finished in a conventional system (CS) and integrated livestock forest (ILF) system with two different densities of eucalyptus trees (ILF-1: 187 and ILF-2: 446 trees/ha). Seventy-two heifers were randomly assigned to three groups, and the animal performance was evaluated during the finishing phase. Forty-eight samples of the longissimus thoracis muscle were collected for the analysis of carcass and meat quality. No differences were found between treatments for final live weight and average daily gain (P > 0.05). The weight gain per ha and carcass weight gain per ha was lower in ILF-2 system in comparison to CS system, which did not differ from ILF-1. However, the stocking rate was higher in CS in comparison to that of the ILF-1 and ILF-2 systems (P < 0.05). Microclimatic variables and thermal comfort indices were better in ILF-1 and ILF-2 systems, except for the wind speed that was higher in CS due to the absence of trees (P < 0.05). Carcass and meat quality did not differ between the evaluated systems (P > 0.05). Only the pH and protein content showed a difference (P < 0.05), but both were within the appropriate range warranting the meat good quality. It is thus concluded that the system with lower tree density does not interfere with the performance and carcass characteristics of heifers. In addition, the systems with trees provide better comfort to the animals and do not affect the quality of their carcass and meat.
Keywords: industrial crossing; longissimus thoracis; silvopastoral systems; tenderness; weight gain